DA’WA AND CONTRIBUTION OF SHAYKH YUSUF AL-MAQASSARĪ IN THE PURIFICATION OF MUSLIM BELIEFS IN SOUTH SULAWESI AND SOCIAL CHANGE - Sahib, Muzdalifah; Sahib, Muhammad Amin; Nur Asiah Kudaedah (Jurnal Dakwah Tabligh, 2025)
This article investigates how Shaykh Yusuf al-Maqassarī’s profile, his da‘wa, and contribution, through the purification of beliefs (aqīda) of Muslims, which is inspired by the author’s research in Indonesia till Leiden, the Netherlands. This article utilized a qualitative descriptive method with a comprehensive religious history approach, for describing and identifying al-Maqassarī’s profile, his da‘wa through the purification of beliefs of the Muslim community that contributes and plays an important role towards social changes in South Sulawesi. The result showed that Shaykh Yūsuf (1626-1699), a moderate ṣūfī from Eastern Indonesia who is still one of the ahl al-Bayt. He wandered to several parts of the world to deepen his understanding of Islamic mysticism. He holds the title ‘wālī quṭb al-Rabbānī wa al-’Árif al-Ṣamaḍānī’ and is well known for his Waḥdat al-Ṣamad view. He was a prolific writer, fighter, and human rights defender until his exile, initially to Ceylon, then to Cape of Good Hope, Cape Town, South Africa. Today, he has become a National Hero of Indonesia and South Africa. His main teaching is the purification of beliefs (aqīda). All practices and worship are directed to the Oneness of God and nothing else. This teaching has become the basis of his reformist ideas, to transform his animistic society into fervent Muslims, especially in South Sulawesi, and then to be implemented into his Ṭarīqat Khalwatiyyat al-Yusufiyya (Yusufiyya). This article will benefit the South Sulawesi community in particular and Indonesia in general, and be a reference for future researchers.